2021
DOI: 10.21203/rs.3.rs-220298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus and Its Impacts on Health Workers Retention: A Systematic Review and Meta-Synthesis

Abstract: Background: The present study aimed to determine the prerequisites and requirements for retention of human resources during the Covid-19 disaster. It was tried in this study to systematically review the challenges and prerequisites, strategies, and measures related to the retention of health workers during the disaster.Methods: This is a systematic review and meta-synthesis of all the articles related to the factors affecting the retention of human resources during the Covid-19 disaster. The articles were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Elsafty and Ragheb (2020) have conducted research on employees in healthcare industry, more specifically from the medical supplies sector, and found that health related and quality of life and access to information and updates on the Pandemic with financial benefits are the most important variables to the retention of employees (p.57). Furthermore, Jamebozorgi et al (2021) conducted a systematic review of 23 articles related to coronavirus impact on health workers retention and synthetized the effects of Covid19 on hospital staff and the retention strategies used by the HR managers and senior management. According to Jamebozorgi et al (2021) the most significant effects of Covid 19 on hospital staff include: violence and stigma against the staff, burnout and stress and increased employee workloads, while the retention strategies include: acquiring communication skills, attention to employees mental and physical health, attention to employee's safety, mobilizing the staff to assist the current forces, expanding cyberspace infrastructures and motivational-health incentives.…”
Section: Previous Research and Healthcare Sector In North Macedoniamentioning
confidence: 99%
See 3 more Smart Citations
“…Elsafty and Ragheb (2020) have conducted research on employees in healthcare industry, more specifically from the medical supplies sector, and found that health related and quality of life and access to information and updates on the Pandemic with financial benefits are the most important variables to the retention of employees (p.57). Furthermore, Jamebozorgi et al (2021) conducted a systematic review of 23 articles related to coronavirus impact on health workers retention and synthetized the effects of Covid19 on hospital staff and the retention strategies used by the HR managers and senior management. According to Jamebozorgi et al (2021) the most significant effects of Covid 19 on hospital staff include: violence and stigma against the staff, burnout and stress and increased employee workloads, while the retention strategies include: acquiring communication skills, attention to employees mental and physical health, attention to employee's safety, mobilizing the staff to assist the current forces, expanding cyberspace infrastructures and motivational-health incentives.…”
Section: Previous Research and Healthcare Sector In North Macedoniamentioning
confidence: 99%
“…Stuart et al (2021). Humphries et al (2021) have noted that "the pandemic intensified and reinforced, rather than radically altered, the dynamics of doctor emigration from Ireland", while Jamebozorgi et al (2021) and Rangachari and Woods (2020) are more focused on strategies and recommendations for staff retention. Nevertheless, this crisis showed that the retention of the most skillful staff should be a central aim of every organization, especially in the healthcare sector.…”
Section: Previous Research and Healthcare Sector In North Macedoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, increased rates of absenteeism reported by HCWs not only contribute to added burden of care for colleagues but more importantly highlight the systemic need for additional support for HCWs [ 18 ]. Meanwhile, reviews suggest that increased workloads, occupational stress and burnout, and organizational changes are expected to pose critical challenges in future to the long-term retention of HCWs [ 19 ]. Taken together, research is urgently needed to understand HCWs’ experiences during the COVID-19 pandemic, including challenges and changes in the workplace, moral-ethical dilemmas, evolving occupational duties, standards of care, service delivery, and the effects of COVID-19 on dimensions of mental health and well-being.…”
Section: Introductionmentioning
confidence: 99%